Evaluation of the effectiveness of VOC-contaminated soil preparation based on AHP-CRITIC-TOPSIS model. (May 2021) - Li, Yuan; Wei, Mingli; Liu, Lei; Yu, Bowei; Dong, Zhiwei; Xue, Qiang
Abstract: Currently, several methods have been adopted for the laboratory preparation of artificial volatile organic compound (VOC) contaminated soils (VCSs). However, it remains unclear whether the prepared contaminated soils are homogenous. In this study, two representative VOCs, toluene and perchloroethylene, were separately mixed with a kaolin-based soil using six preparation methods. Thereafter, the homogeneity and recovery of the contaminated kaolin prepared using these methods were determined and analyzed. The six procedures were quantitatively assessed according to the comprehensive evaluation mathematical model (AHP-CRITIC-TOPSIS), and the final score order of the different procedures was: A > C > E > B > F > D. Additionally, the qualitative evaluation of the procedures was performed based on the phase transformation and mass transfer during the mixing processes. Based on these discussions, method A, which was considered to be optimal, was then adopted for further investigations with various natural soils. The results showed that this optimal method could be applied to natural soils and revealed that the adsorption-related characteristics of natural soils, including total organic carbon, specific surface area, pore volume, pH, plastic limit, particle size, and mineral composition, influenced the homogeneity and recovery through mass transfer. In addition, it was also observed that the chemical properties of VOCs, including molecular structure, vapor pressure, and the octanol/water partition coefficient, could also affect the effectiveness of sample recovery. Through this study, researchers can prepare VCSs with excellent homogeneity and low loss rates to conduct standardized tests for technology development. Graphical abstract: Image 1 Highlights: Homogeneity (CV) and recovery (RR) are used to evaluate preparation effectiveness. AHP-CRITIC-TOPSIS model obtains the optimal method by scoring (highest score, 0.857). Applying optimal method to natural soil is feasible, its recovery is often high. Soil adsorption-related property has effect on sample preparation ( r  = 0.848–0.991).